DETERMINAN FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Reza Yolanda; Ricky A. Mulyana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to determine the effect of current assets, retained earnings to total assets, earnings before interest and tax to total assets, debt to assets ratio, total assets turnover, managerial ownership, and institutional ownership on financial distress. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange consistently from 2019 to 2021. This research uses purposive sampling method in selecting the sample, there are 84 manufacturing companies listed on the Indonesia Stock Exchange which are the sample of this research. Logistic regressions model is used to analyze this research data. The result of the study indicates that earnings before interest and tax to total assets has influence on financial distress, which means that when the company is able to effectively use its fixed assets and generates profit, the company is able to pay its obligations in current period and reduces the probability of experiencing financial distress. However, current assets, retained earnings to total assets, debt to assets ratio, total assets turnover, managerial ownership, and institutional ownership do not have any influence on financial distress.